Functionalized carbon nanotubes for anticancer drug delivery. (September 2011) - Lay, Chee Leng; Liu, Jing; Liu, Ye
In vitro and in vivo results reflect that functionalized carbon nanotubes (f-CNTs) are promising for the development of unique delivery systems of anticancer drugs. Functionalization of CNTs and drug loading are realized by covalent attachment and/or physical approaches. Poly(ethylene glycol) is the most adopted species for functionalization, which can increase the dispersity in aqueous solution and biocompatibility of CNTs. Several types of anticancer drugs, such as paclitaxel and doxorubicin, are loaded onto f-CNTs and their treatment efficacy has been demonstrated in vitro and in vivo . However, f-CNTs of well-controlled structures, such as uniform length and well-defined chemistry, which are not available so far, are important to solve the current controversy over the mechanisms of cell uptake of f-CNTs, and are a prerequisite to investigate whether f-CNTs can be platform materials for anticancer drug delivery with improved efficacy.